2006
DOI: 10.1182/blood-2005-11-4503
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of reduced-intensity conditioning and conventional high-dose conditioning for allogeneic hematopoietic stem cell transplantation using HLA-identical sibling donors in myelodysplastic syndromes

Abstract: In this multicenter retrospective study, the outcomes of 836 patients with myelodysplastic syndrome (MDS) who underwent transplantation with a human leukocyte antigen (HLA)-identical sibling donor were analyzed according to 2 types of conditioning: reduced-intensity conditioning (RIC) in 215 patients, and standard myeloablative (or high-dose) conditioning (SMC) in 621 patients. In multivariate analysis, the 3-year relapse rate was significantly increased after RIC (hazard ratio [HR], 1.64; 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(215 citation statements)
references
References 40 publications
10
196
4
3
Order By: Relevance
“…In this setting, the efficacy of SCT relies essentially on a potent GvL. Most retrospective studies have shown similar outcomes between RIC/NMA and conventional myeloablative conditioning (MAC), but with more relapse with RIC and NMA, and more toxicity with the conventional approach [16,17]. However, AML appears to be less sensitive to the GvL than other diseases such as chronic myelogenous leukemia [18], and some degree of dose intensity has been shown as important in the outcome of AML [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, the efficacy of SCT relies essentially on a potent GvL. Most retrospective studies have shown similar outcomes between RIC/NMA and conventional myeloablative conditioning (MAC), but with more relapse with RIC and NMA, and more toxicity with the conventional approach [16,17]. However, AML appears to be less sensitive to the GvL than other diseases such as chronic myelogenous leukemia [18], and some degree of dose intensity has been shown as important in the outcome of AML [19].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously these studies are limited by the fact that fitter patients were probably more often proposed myeloablative regimens, while older and sicker patients were given nonmyeloablative or RIC regimens. Nevertheless, these studies found similar disease-free and overall survivals in the two groups of patients, since non-relapse mortality was lower in nonmyeloablative patients, but relapse rates were lower in myeloablative recipients [23][24][25].…”
Section: Comparison Of Outcomes After Myeloablative or Ric Regimensmentioning
confidence: 81%
“…Three large retrospective studies from the EBMT have compared HSCT outcomes of patients given various myeloablative versus various RIC/nonmyeloablative regimens as treatment for AML, MDS, or chronic lymphocytic leukemia (CLL) ( Table 1) [23][24][25]. Obviously these studies are limited by the fact that fitter patients were probably more often proposed myeloablative regimens, while older and sicker patients were given nonmyeloablative or RIC regimens.…”
Section: Comparison Of Outcomes After Myeloablative or Ric Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…39 A report by Martino et al on results in 621 patients conditioned with high-dose and 215 patients prepared with reducedintensity conditioning (RIC) regimens (including patients in all MDS categories) showed a significantly higher 3-year relapse rate (HR 1.64; p=0.001) but a significantly lower NRM (HR 0.61; p=0.015) in RIC patients. 40 As a result, 3-year RFS was comparable, 39% and 33% for high dose and RIC, respectively (Figure 1). It is important to note that RIC patients were older (73% versus 28% >50 years; p< 0.001) and had more adverse pre-HCT conditions, a pattern also present in other studies.…”
Section: Choosing a Translpant Regimenmentioning
confidence: 83%